Establishing nitrogen acquisition strategies of Bejaria resinosa Mutis ex L. (Ericaceae) from low fertility soils of Colombia (2023)
• A key question about plants’ interaction with their environment is which strategies do they have for nutrient acquisition. We aimed to determine the different mechanisms used by Bejaria resinosa to obtain nitrogen. Carnivory, mutualism with insects and mycorrhizas were potential pathways tested in this study. • We compared nitrogen and carbon natural isotopes from apical organs and roots of B. resinosa with isotopes from carnivorous plants, ericoid mycorrhizal plants, arthropods, and fungi. We also, performed an ecological and anatomically characterization of the plant using electronic microscopy, protease production tests and field observations of arthropods’ interactions. • Organs of B. resinosa showed differentiation in their carbon and nitrogen isotopic signatures. We did not find significant differences in the 15N signature of B. resinosa compared with carnivorous plants, but found statistical differences in the 13C. Diptera and Hymenoptera were usual insects’ orders found trapped in Bejaria’s flowers and leaves. We found glandular and non-glandular trichomes in Bejaria’s leaves. • Comparisons of the isotopic signature of B. resinosa with carnivorous plants suggests that B. resinosa could obtain N from an 15N enriched source such as arthropods trapped on its apical organs. Even though plant isotopic signature could be affected by several ecological factors, the evidence compiled in this study suggests a potential case of holocarnivory of B. resinosa. Holocarnivory could observed in plants in the absence of protease production and pores in the leaf cuticle. Experimental studies are necessary to confirm if B. resinosa is a carnivorous plant